Cooperative Performance from Financial Aspects and Interest-Free Loan Strategy to Increase Member Loyalty - Akhmad Sefudin; Hendro Prasetyono; Ira Pratiwi Ramdayana; Ray Pangestu; Amirah Shazana; Hamdan Daniel (Jurnal Pemberdayaan Masyarakat, 2026)
The purpose of this study is to determine the performance of Koperasi Pegawai UNINDRA (KOPPINDRA) or UNINDRA Employee Cooperative in terms of financial performance, loyalty, and interest-free loans. The research approach used is a mix of quantitative and qualitative methods. The quantitative approach is used to analyze KOPPINDRA's income statement from 2022 to 2024. Customer loyalty was measured using a questionnaire distributed to 105 customers from a total of 904 KOPPINDRA members. The qualitative approach using FGD aims to deepen the findings of the financial analysis and to explore the dimensions of customer loyalty. Financial performance indicators, including the current ratio, debt-to-assets ratio, debt-to-equity ratio, and total asset turnover, are good, so they must at least be maintained. Aspects of return on equity, net profit margin, and return on assets still need improvement. The highest indicator of KOPPINDRA customer loyalty is the willingness to be a long-term customer. The highest-scoring dimension, on average, was trust, and the lowest-scoring dimension was recommendation. KOPPINDRA should maintain its no-fee loan policy to retain customer loyalty and encourage cash use for transactions.